Interaction Hegemony in Soccer Diplomacy: Social Media Communication Strategies of Four AFC Champions League Two Clubs - Ridha Handayani; Rini Sudarmanti (Publikasi Indonesia, 2026)
This research analyzes the social media communication strategies of four Southeast Asian football clubs in the AFC Champions League Two Group G competition, namely Persib Bandung (Indonesia), Selangor FC (Malaysia), True Bangkok United (Thailand), and Lion City Sailors (Singapore). The study used a content analysis method on 1,349 uploads during the period of November 27-December 10, 2025. The results of the study found